2015
DOI: 10.1007/s00580-015-2114-z
|View full text |Cite
|
Sign up to set email alerts
|

Sub-acute toxicity of lantadenes isolated from Lantana camara leaves in guinea pig animal model

Abstract: The sub-acute toxicity of lantadenes isolated from Lantana camara leaves was studied in guinea pig laboratory animal model. A total of 20 guinea pigs of either sex were divided into five groups. Group I served as control, while groups II, III, IV, and V were orally administered lantadenes at the dose rate of 100, 50, 25, and 12.5 mg/kg body weight (bw), respectively for 28 days. The levels of aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, acid phosphatase, total bilirubin, blood ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 23 publications
3
15
0
Order By: Relevance
“…However, ictericity was not observed in sub-chronic toxicity as the biliary mechanism is least altered and can be compared with minimal effect of lantadenes on the values of ALP, which gives a clear evidence for no development of cholestatic mechanism and ictericity in animals. But the presence of lower doses of this toxin in circulation might be capable to cause more sub-chronic changes and degenerations, which were minimal in previous studies on acute and sub-acute lantadenes exposure [ 2 , 7 ].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, ictericity was not observed in sub-chronic toxicity as the biliary mechanism is least altered and can be compared with minimal effect of lantadenes on the values of ALP, which gives a clear evidence for no development of cholestatic mechanism and ictericity in animals. But the presence of lower doses of this toxin in circulation might be capable to cause more sub-chronic changes and degenerations, which were minimal in previous studies on acute and sub-acute lantadenes exposure [ 2 , 7 ].…”
Section: Discussionmentioning
confidence: 98%
“…The changes in the liver specific serum enzymes indicated significant hepatic damage and were well supported by histopathological alterations in the liver. The previous study on sub-acute lantadene toxicity in guinea-pigs showed an increase in the values of ALT, AST, and ALP while no significant increase was seen in ACP levels [ 7 ]. Sharma and Sharma [ 32 ] reported that the oral administration of LA to guinea pigs elicited an increase in activities of ALT, AST, ALP and ACP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The animals are died within 2-4 days in acute cases. In sub acute lantadene toxicity study a dose dependent mortality was reported (Parimoo et al, 2015). Sluggishness, weakness, bloody diarrhea, edematous ears and eyelids, cracks and fissurs on muzzle and other non-hairy parts, conjunctivitis, ulceration of the tip and under surface of the tongue (if un-pigmented), pale conjunctival, vulvar or vaginal mucous membranes and sclera of eye are some of the clinical signs observed in lantana toxicity.…”
Section: Absorption and Mechanism Of Action Of Lantadenesmentioning
confidence: 99%
“…The LD50 value of lantadene in sheep is 1-3 mg/kg body weight, when administered by intravenous route, while the LD50 value is 60 mg/kg body weight when administered by oral route, because of show absorption (Nellis, 1997). The oral administration of lantadenes at the dose rate of 25 mg/kg body weight did not lead to mortality in guinea pigs, but produced hepatotoxic and nephrotoxic effects which were evident on histopathology and on biochemical estimation and were indicative of sub-acute toxicity (Parimoo et al, 2015). Transfer of lantana toxins to milk, placenta, or to the offspring has not been reported, but some teratological effects has been seen in rats (Mello et al, 2005;Sharma et al, 2007).…”
Section: Absorption and Mechanism Of Action Of Lantadenesmentioning
confidence: 99%